The Effect of Working Capital Turnover and Inventory Turnover on Profitability on CV. Cita Mandiri, Junrejo Sub-Regency, Batu City - Elfrida Fatima Ida; Elly Lestari; Moch Nurhidayat (International Journal of Management and Business, 2025)
High profitability describes the company's success in managing the company's operations. Factors that support the increase in profitability are inventory turnover and working capital. The following research aims to determine the impact of inventory turnover and working capital turnover on profitability in CV Cita Mandiri, Junrejo District, Batu City in a partial and simultaneous way. The following research was carried out using quantitative techniques. The data source in the following research is the financial statements of CV Cita Mandiri, Junrejo District, Batu City for five periods, namely 2019 to 2023. The data analysis technique carried out is multiple linear regression. With a t-value of 5.465 for working capital turnover and a t-value of 5.206 for inventory turnover, the results of the following study explain that these two factors have a significant influence on profitability. Inventory turnover and working capital turnover together have a great influence on profitability on CV Cita Mandiri, Junrejo District, Batu City. with an F value = 11.246 or an influence of 91.8%. This result can be understood that the higher the working capital turnover and inventory turnover are able to support the increase in the company's profitability.